Pengalaman Perawat yang Mengalami Tindak Kekerasan oleh Klien Skizofrenia - Muhammad Amin; Susilawati Susilawati; Wulan Angraini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine how the experience of nurses who experience acts of violence by schizophrenic clients. The type of research used in this research is qualitative, which intends to explain and provide understanding and interpretation of various behaviors and experiences of humans (individuals) in multiple forms. The study results produced several themes, namely the form of violence, the condition of the patient, preventive measures, the state of the nurse when receiving violence, the health condition of the nurse, and the time the patient was angry. In conclusion, the violence experienced by nurses was being hit, pulled, thrown using a food holder, and spat on. The patient's condition who commits acts of violence is that the patient's hallucinations are occurring, the patient is unstable, and the medicine is not taken. Keywords: Nurse Experience, Schizophrenia, Violence